Resepsi qur’an dan gerakan sosial-keagamaan nahdhatul wathan di Lombok, Indonesia - Syamsul Wathani (Al Irfani: Journal of Al Qur'anic and Tafsir, 2022)
In people's lives, the Koran is treated not only as reading material, study, and decoration but more than that the reality of society treats hadith as a variety of behaviors, such as: drugs, and motivation in carrying out certain worship. On the other hand, there are verses of the Koran that are turned on to renew the social condition of a society, whether it is done by a person or by a particular community or organization. This article discusses the Nahdlatul Wathan (NW) organization, looking at the Koran that lives in the movement and development of the organization. The analysis in this article uses the theory of collective action social movements promoted by Antony Giddens. This article finds that conclusion. As an organization engaged in da'wah and education, Nahdlatul Wathan (NW) uses the Koran as a spirit in struggle and movement. The main principles of the organization in the form of faith and piety are taken from QS. Ali-Imran 102 and al-Hujurat 13, these verses became the initial motivation as well as the basis for preaching. While the verses related to Belief, Ikhlas, and Istiqomah serve as guidelines in mobilizing all fields of Da'wah, education, and social affairs.